Ferric Pyrophosphate in Extruded, Fortified Rice Leads to Better Iron Outcomes Than Ferric Phosphate in Rats (P24-014-19). (13th June 2019) - Ward, Erin; Suleria, Hafiz; Joseph, Michael; Alavi, Sajid; Lindshield, Brian
Abstract: Objectives: Rice fortification is a promising approach to reduce micronutrient deficiencies. Ferric phosphate (FePO4 ) and ferric pyrophosphate (FePP) have been suggested iron forms for their suitable organoleptic properties. Micronized FePP or the addition of citric acid (CA) and trisodium citrate (TSC) to FePP have been suggested to increase FePP bioavailability. Our primary objective was to compare iron bioavailability of extruded rice with these four iron fortificants. Methods: Rice flour was fortified with a USDA MR24 vitamin/mineral blend and one of four iron fortificants: FePO4, FePP, micronized FePP, or FePP with CA and TSC (FePP + CA + TSC, ratio 1:0.1:2.1). Each extruded rice was blended at a 1:100 ratio with unenriched white rice. Soy protein isolate and soybean oil were added to the diets to meet growing rat nutritional requirements (15 g protein and 5 g fat/100 g diet) and cooked to approximately 40% added moisture content. Daily food intake and weekly body weights were measured in five groups (AIN-93 G or rice) of weanling, male Sprague Dawley rats ( n  = 10). Each group consumed assigned diet for 21-days, when the study was terminated because of poor growth in the rice groups. Blood and livers were collected to evaluate iron outcomes and bone mineral density (BMD) and body composition were assessed with PIXImus scans. Results: All rice groups had significantly lower moisture-adjusted total food intake, weight gain, final weight, and BMD compared to the AIN-93 G group with no differences in these outcomes between the rice groups. There were no differences in either iron outcome between the different FePP fortificants. Hemoglobin levels were significantly higher in the FePP and micronized FePP groups compared to the FePO4 and AIN-93 G groups. Hepatic iron levels were significantly higher in the FePP, micronized FePP, and FePP + CA + TSC groups compared to the FePO4 and AIN-93 G groups. Conclusions: While they need to be interpreted with some caution because of poor growth, our results suggest that FePP leads to better iron outcomes than FePO4 . However, neither micronizing nor adding CA + TSC to FePP improved iron outcomes. Funding Sources: Partially funded by the USDA Foreign Agricultural Service under the Micronutrient Fortified Food Aid Products Pilot (MFFAPP) program and the Kansas Agricultural Experiment Station.